Radical reproductive justice: Foundation, theory, practice - Ross, Loretta; Roberts, Lynn; Derkas, Erika; Peoples, Whitney; Bridgewater Toure, Pamela (Feminist press, 2017)
Expanding the social justice discourse surrounding "reproductive rights" to include issues of environmental justice, incarceration, poverty, disability, and more, this crucial anthology explores the practical applications for activist thought migrating from the community into the academy. Radical Reproductive Justice assembles two decades’ of work initiated by SisterSong Women of Color Health Collective, creators of the human rights-based “reproductive justice” framework to move beyond polarized pro-choice/pro-life debates. Rooted in Black feminism and built on intersecting identities, this revolutionary framework asserts a woman's right to have children, to not have children, and to parent and provide for the children they have.
Keywords: afro-féminisme; approches et analyses; discipline; droit; droits des femmes*; intersectionnalité; justice reproductive; justice sociale; maternité; militance; santé; science politique et droit; sciences humaines; sociologie; sofia; thématiques

Le droit criminel, la justice transformatrice et la violence faites aux femmes : regards croisés - Chagnon, Rachel; Côté, Liliane; Mickaelian, Virginie (Ligue des Droits et Libertés, 2015)
Number: 1
Keywords: 1900-1999; 2000 à aujourd'hui; amérique du nord; amériques; canada; changement social; discipline; droit; droit criminel; histoire et politique; justice réparatrice; périodes historiques; québec; ressource en ligne; régions géographiques; science politique et droit; sofia; thématiques; violences; violences conjugales; violences sexuelles

A broader vision of the reproductive rights movement: Fusing mainstream and latina feminism - Hooton, Angela (American University Journal of Gender, Social Policy & the Law, 2005)
https://digitalcommons.wcl.american.edu/cgi/viewcontent.cgi?article=1284&context=jgspl
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 2000-2009; amériques; approches et analyses; discipline; discours dominant; droit; droits des femmes*; femmes* latino-américaines; histoire et politique; justice reproductive; justice sociale; militance; ressource en ligne; régions géographiques; santé; santé reproductive; science politique et droit; systèmes d'oppression; thématiques; états-unis